A scoping review on the role of virtual walking intervention in enhancing wellness - Yushen Dai; Jiaying Li; Yan Li; Frances Kam Yuet Wong; Mengqi Li; Chen Li; Ye Jia; Yueying Wang; Janelle Yorke (npj Digital Medicine)
Abstract Virtual walking has the potential to be an adjunct to traditional physical therapy. This scoping review aims to synthesize evidence on the characteristics, effectiveness, feasibility, and neurological mechanism of virtual walking interventions on health-related outcomes. Articles in English were retrieved from twelve databases (January 2014–October 2024). Thirteen interventional studies were included, focusing on three types of virtual walking: passive observing moving (71.4%), arm swing locomotion (21.5%), and foot tracking locomotion (7.1%). Most studies (84.6%) involved individuals with spinal cord injuries, while the remaining studies focused on lower back pain (7.7%) and lower limb pain (7.7%). Over 70% of studies lasted 11–20 min, 1–5 weekly sessions for 10–14 days. Statistically significant findings included pain reduction (84.6%), improved physical function (mobility and muscle strength), and reduced depression. Mild adverse effects (fatigue and dizziness) were transient. Neurological evidence indicates somatosensory cortex activation during virtual walking, possibly linked to neuropathic pain.